2018
DOI: 10.3390/ijms19010241
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Verticillium Wilt Resistance by Applying Arbuscular Mycorrhizal Fungi to a Cotton Variety with High Symbiotic Efficiency under Field Conditions

Abstract: Arbuscular mycorrhizal fungi (AMF) play an important role in nutrient cycling processes and plant stress resistance. To evaluate the effect of Rhizophagus irregularis CD1 on plant growth promotion (PGP) and Verticillium wilt disease, the symbiotic efficiency of AMF (SEA) was first investigated over a range of 3% to 94% in 17 cotton varieties. The high-SEA subgroup had significant PGP effects in a greenhouse. From these results, the highest-SEA variety of Lumian 1 was selected for a two-year field assay. Consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 82 publications
2
29
0
Order By: Relevance
“…AMF diversity and colonisation reduced with increases the years of conventional fertilisation, which decreased both the P absorption and the disease resistance of plants in the field (Lin et al, ). AM colonised seedlings of strawberry and cotton can bring AMF into the field and take physiological functions in the field (Stewart et al, ; Zhang et al, ). In this study, nursery cultivating watermelon seedlings with AMF was found maintaining high levels of AMF colonisation and enhancing AMF spore density in rhizosphere soil in the field.…”
Section: Discussionmentioning
confidence: 99%
“…AMF diversity and colonisation reduced with increases the years of conventional fertilisation, which decreased both the P absorption and the disease resistance of plants in the field (Lin et al, ). AM colonised seedlings of strawberry and cotton can bring AMF into the field and take physiological functions in the field (Stewart et al, ; Zhang et al, ). In this study, nursery cultivating watermelon seedlings with AMF was found maintaining high levels of AMF colonisation and enhancing AMF spore density in rhizosphere soil in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al studied the positive role of the arbuscular mycorrhizal fungus Rhizophagus irregularis CD1 on plant growth promotion and the Verticillium wilt resistance of cotton [ 5 ]. They determined the symbiotic efficiency of 17 cotton varieties to R. irregularis .…”
Section: The Good: Soil Microbes Positively Affecting Plant Growthmentioning
confidence: 99%
“…Presence of the mycorrhizal fungus significantly increased plant growth and plant disease resistance against Verticillium dahliae wilt. While the negative effect on V. dahliae colonization could be due to mycorrhiza-induced resistance, the authors show that growth of R. irregularis may directly inhibit growth of V. dahliae by releasing as yet unknown volatiles [ 5 ].…”
Section: The Good: Soil Microbes Positively Affecting Plant Growthmentioning
confidence: 99%
“…Conventional management for cotton VW disease is an integrated approach that includes planting resistant cultivars, extending cultural practices [3] , managing water and fertilizer [9] , and biocontrol with fungicidal bacteria [10] . Among these, breeding resistant varieties is considered the most effective and economical approach to controlling this disease.…”
Section: Introductionmentioning
confidence: 99%